Orthodontic Camouflage Treatment of Class II Malocclusion in Non-growing Patient - A Case Report (Orthodontic Journal of Nepal, 2015)
The prevalence of skeletal Class II malocclusion is high amongst Asian population. Various treatment modalities have been presented for the treatment of Class II malocclusions in adult patients. We come across many adult patients who desire a costeffective and non-surgical correction and they accept dental camouflage as a treatment option to mask skeletal discrepancy. This case report presents a 26-year-old non-growing female who had a skeletal Class II malocclusion with prognathic maxilla and retrognathic mandible with an overjet of 7 mm, severe crowding, but did not want surgical treatment. We considered the camouflage treatment by extracting upper first premolars. Following the treatment, a satisfactory result was achieved with an acceptable static and functional occlusion, facial profile, smile and lip competence with patient satisfaction.